2017
DOI: 10.1021/acsami.7b10967
|View full text |Cite
|
Sign up to set email alerts
|

Promising Approach for High-Performance MoS2 Nanodevice: Doping the BN Buffer Layer to Eliminate the Schottky Barriers

Abstract: Reducing the Schottky barrier height (SBH) of metal-MoS interface with no deteriorating the intrinsic properties of MoS channel layer is crucial to realize the high-performance MoS nanodevice. To realize this expectation, a promising approach is present in this study by doping the boron nitride (BN) buffer layer between metal electrode and MoS channel layer. Results demonstrate that no matter the types of concentrations and dopants the intrinsic electronic structure, low electron effective mass of MoS channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 62 publications
(125 reference statements)
2
10
0
Order By: Relevance
“…Another study by Su et al suggested that the SBH for both electrons and holes in the metal/hBN/MoS 2 contact geometry can be decreased or even completely eliminated by doping the hBN buffer layer with high concentrations of Li (electron-poor) and O (electron-rich) dopants, respectively, and that this effect can be more pronounced when the doped-hBN buffer layer spreads all over the MoS 2 device surface. Moreover, the authors predicted that both the intrinsic nature of the MoS 2 and the weak FLP effects at the metal/hBN/MoS 2 interface are preserved irrespective of the dopant type and concentration [245].…”
Section: Use Of Interfacial Contact "Tunnel" Barriersmentioning
confidence: 99%
“…Another study by Su et al suggested that the SBH for both electrons and holes in the metal/hBN/MoS 2 contact geometry can be decreased or even completely eliminated by doping the hBN buffer layer with high concentrations of Li (electron-poor) and O (electron-rich) dopants, respectively, and that this effect can be more pronounced when the doped-hBN buffer layer spreads all over the MoS 2 device surface. Moreover, the authors predicted that both the intrinsic nature of the MoS 2 and the weak FLP effects at the metal/hBN/MoS 2 interface are preserved irrespective of the dopant type and concentration [245].…”
Section: Use Of Interfacial Contact "Tunnel" Barriersmentioning
confidence: 99%
“…12,13 Metal-modified MoS 2 materials have been investigated for application in gas molecules adsorption, which shows a broad application prospect. 1416 Furthermore, based on the first-principles calculations, researchers verified that a noble metal-modified MoS 2 monolayer shows great adsorption ability toward specific gas molecules. 15,17 For MoS 2 modification, Wang et al studied the adsorption and diffusion of noble metal atoms on MoS 2 based on the density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 98%
“…In the former case, studying the dependence of the Schottky barrier on the used electrode is crucial [64][65][66][67][68][69][70][71] . It turns out that a hBN tunnel barrier is also a good choice here, preserving the intrinsic properties of the TMDC while enormously reducing the contact resistance 65,[72][73][74] . Also other insulating barriers, such as TiO 2 , MgO or Al 2 O 3 [75][76][77][78][79] are promising candidates, where the thickness of the barrier plays an important role for the efficiency of spin injection.…”
Section: Introductionmentioning
confidence: 99%